Portosinusoidal Vascular Disorder: When to Suspect and How to Manage? - Shalaby, Sarah; Ramírez-Quesada, Wagner Enrique; Ojeda, Asunción; Perez-Campuzano, Valeria; Baiges, Anna; Turon, Fanny; Fuster, Carla; Díaz, Alba; Hernández-Gea, Virginia; García-Pagán, Juan Carlos (Seminars in Liver Disease, 2025)
Portosinusoidal vascular disorders (PSVD) represent a group of rare conditions characterized by abnormalities in the liver's vascular architecture, often manifesting with clinical features of portal hypertension (PH), in the absence of cirrhosis. The pathophysiology of PSVD remains unclear, but it is frequently linked to underlying immunological disorders, medications, hematological disorders, and thrombophilia. Laboratory tests typically show preserved liver function with or without slight alteration on the transaminase profile. A key diagnostic feature is the presence of clear signs of PH alongside normal or only slightly elevated liver stiffness and hepatic venous pressure gradient. Liver biopsy remains essential for confirming the diagnosis and excluding other causes of PH and cirrhosis. However, histological examination may reveal subtle or mild changes, making expert pathological analysis and high-quality specimens crucial for an accurate diagnosis. In some cases, characteristic histological findings may be identified in patients without overt PH, which could represent an early stage of the disease. The long-term prognosis for patients with PSVD is mainly influenced by severity of the underlying condition and development of PH. However, treatments that modify the disease's natural history are still lacking, and management primarily focuses on controlling complications related to PH. Further research into the pathogenesis and potential therapeutic strategies for PSVD is needed to improve patient outcomes.
Keywords: idiopathic noncirrhotic portal hypertension; noncirrhotic portal vein thrombosis; nodular regenerative hyperplasia; portal obliterative venopathy; incomplete septal fibrosis